A Study on the Seventh Grade Students Reading Comprehension Ability of Descriptive Texts at SMPN 6 Jember - Febriana, Fanny; Istianah, Wiwiek; Sukmaantara, I Putu (Jurnal Edukasi Universitas Jember, 2014)
Abstrak. Reading is very important for the students in learning English, especially for the students. The students are able to comprehend what they read to get the ideas and make a conclusion about the information from the text as intended by the writer. The design of this research was descriptive qualitative research. This research began by conducting a preliminary study by interviewing the English teacher of the seventh grade students of SMPN 6 Jember. The data of this research were collected from the students of reading comprehension ability test that was analyzed by using the formula. The result of the students reading comprehension ability of descriptive texts covering word comprehension, sentence comprehension, paragraph comprehension and text comprehension were showed the highest percentage of four indicators was word comprehension with the percentage 83.08% which belonged to the âvery goodâ category and the lowest percentage was the text comprehension with the percentage 57.89% that was classified as âpoorâ category. It showed that the teaching English in reading comprehension ability of descriptive texts needs to be developed especially in the lowest category that was belonged to text comprehension. Â  Keywords : Descriptive Research, Descriptive Texts, Reading Comprehension Ability.